Canais de distribuição: levantamento da percepção dos clientes em relação ao Broker em uma empresa do Distrito Federal - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
In this study, we pursue to examine customer satisfaction towards logistics’ brokerage freight forwarding, through an inquiry into their perception with regard to their brokers’ performance. New distribution patterns, within the field of logistics, emerge as alternative processes, largely benefiting retail outlets’ supply chains, with highlight to logistics brokerage, for its potential to enhance the industry’s resourcefulness to meet customized retail outlet’s demands. Customer’s perception is germane for the logistics industry, and environmental scanning on its products and services allows businesses to exploit opportunities and enhance competitive performance. Our theoretical background, construes from the assessment of distribution channels’ main features, structures and roles, as well as relationship marketing strategies. In order to measure customers’ satisfaction regarding brokerage services in distribution channels’ main features, we organized questions reflecting their key performance indicators. We conducted a survey research based on Nielsen’s checkout heuristics, with 352 respondents from the Brazilian Supermarket industry located in the Federal District. Data obtained, were processed and validated through statistical analysis and consistency checking, bringing about, among other data, descriptive statistics (frequency and relative frequency distribution; mean and standard deviation) as well as correlation analysis (coefficient of variation; Pearson’s skewness and correlation coefficients). Construing from an in-depth exploration of our survey, in light of our methodological background, our findings suggest an overall customer satisfaction towards brokerage services in the industry. Some insights, were developed from our findings in terms of key customers’ perceptions, giving room to recommendations for further research, which could provide the enhancement of competitive advantages for firms in the industry.
Keywords: Canais de distribuição; Broker; Percepção; Satisfação; Distribution channels; Broker; Perception; Satisfaction; ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS